PASCal: a principal axis strain calculator for thermal expansion and compressibility determination - Cliffe, M; Goodwin, A (2012)
This article describes a web-based tool (PASCal; principal axis strain calculator; http://pascal.chem.ox.ac.uk) designed to simplify the determination of principal coefficients of thermal expansion and compressibilities from variable-temperature and variable-pressure lattice parameter data. In a series of three case studies, PASCal is used to reanalyse previously published lattice parameter data and show that additional scientific insight is obtainable in each case. First, the two-dimensional metal-organic framework [Cu2(OH)(C8H3O7S)(H2O) ]·2H2O is found to exhibit the strongest area negative thermal expansion (NTE) effect yet observed; second, the widely used explosive HMX exhibits much stronger mechanical anisotropy than had previously been anticipated, including uniaxial NTE driven by thermal changes in molecular conformation; and third, the high-pressure form of the mineral malayaite is shown to exhibit a strong negative linear compressibility effect that arises from correlated tilting of SnO6 and SiO4 coordination polyhedra. © 2012 International Union of Crystallography Printed in Singapore-all rights reserved.